2019
DOI: 10.1002/joc.6438
|View full text |Cite
|
Sign up to set email alerts
|

Interdecadal variation of frequencies of tropical cyclones, intense typhoons and their ratio over the western North Pacific

Abstract: This study explores whether a higher frequency of tropical cyclone (TC) occurrence would lead to more intense typhoons (ITYs) over the western North Pacific (WNP) during 1975–2016. The proportion of ITYs shows an upward trend, with a low‐ (1975–2001) and a high‐proportion period (2002–2016). There is an interdecadal variation in TC and ITY frequencies within the period 1975–2001, with three subperiods (1975–1986, 1987–1997 and 1998–2001) identified. Both the annual frequencies of TCs and ITYs are below normal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 37 publications
1
7
0
Order By: Relevance
“…This indicates that recent TC landfall locations in Japan tend to shift northeastward in Japan. It may be influenced by atmospheric circulation conditions over the WNP during 1977-2019 (Liu and Chan 2019). However, the increasing tendency during 1977-2019 seems that it includes within a fluctuation in the 100-year time scale variability from our 143 years data analysis.…”
Section: Tc Landfall In Japanmentioning
confidence: 65%
“…This indicates that recent TC landfall locations in Japan tend to shift northeastward in Japan. It may be influenced by atmospheric circulation conditions over the WNP during 1977-2019 (Liu and Chan 2019). However, the increasing tendency during 1977-2019 seems that it includes within a fluctuation in the 100-year time scale variability from our 143 years data analysis.…”
Section: Tc Landfall In Japanmentioning
confidence: 65%
“…Murakami et al (2020) showed a clear poleward shift of TC frequency along the east China coast for 1980-2018. Liu and Chan (2019) found that the mean landfall intensity is increasing at the east coast of China due to more frequent landfalls by intense typhoons.…”
Section: Discussionmentioning
confidence: 99%
“…Klotzbach and Landsea (2015) found a flattening out of the increasing trend for the very intense TCs (V max ⩾ 113 kt) reported by Webster et al (2005), after extending the dataset of Webster et al (2005) by ten years, but the increasing tendency for both intense and very intense TCs is still unchanged. In a recent study by Liu and Chan (2019), the frequencies of TC genesis and of very intense TC occurrence were certainly shown to be not necessarily correlated.…”
Section: Introductionmentioning
confidence: 95%
“…However, this does not mean that we can draw the same conclusion with confidence in a particular ocean basin. For example, an increasing trend in the North Atlantic (NA) ocean basin in recent decades (Mann andEmanuel 2006, Bruyère et al 2012) and an abrupt decrease in the western North Pacific (WNP) ocean basin near the end of the 20th century (Liu and Chan 2013, 2019, He et al 2015, Hu et al 2018, Zhao et al 2018b have been reported. Why does the TC genesis frequency have a particular trend in these ocean basins?…”
Section: Introductionmentioning
confidence: 99%